TRANSFORMASI UPAYA ADMINISTRATIF DALAM PENYELESAIAN SENGKETA KEPEGAWAIAN - Marbun, Robinsar (Jurnal Yuridis, 2017)
Civil Service dispute is a dispute/dispute arising as a result of the stipulation of a State Administrative Decision in the field of personnel by the Authorized Body or Official regarding the position, obligation, right and guidance of Civil Servants. While Administrative Efforts is a procedure that can be taken by Civil Servants who are not satisfied with disciplinary punishment imposed on him in the form of objection or administrative appeal. The objection itself is an administrative effort that can be taken by the Disgruntled Civil Servant against disciplinary punishment imposed by the competent authority to punish the superior officer in charge of punishment. For Administrative Appeals alone it is an administrative undertaking that a disgruntled  Civil Servant may take with respect to disciplinary punishment in the form of dismissal with respect not on his own request or dismissal with respect as a Civil Servant imposed by a punitive authority to the Employment Advisory Board